Low-intensity resistance exercise does not affect cardiac autonomic modulation in patients with peripheral artery disease (Clinics, 2013)
OBJECTIVE: To analyze the effect of a single bout of resistance exercise on cardiac autonomic modulation in patients with peripheral artery disease. METHODS: Fifteen patients with peripheral artery disease (age: 58.3±4.0 years) underwent the following sessions in a random order: resistance exercise (three sets of 10 repetitions of the six resistance exercises with a workload of 5-7 in the OMNI-RES scale) and control (similar to the resistance session; however, the resistance exercises were performed with no load). The frequency domain (low frequency, high frequency and sympathovagal balance) and symbolic analysis (0V, 1V and 2V patterns) of heart rate variability were obtained before and until one hour after the interventions. RESULTS: After the resistance exercise and control sessions, similar increases were observed in the consecutive heartbeat intervals (control: 720.8±28.6 vs. 790.9±34.4 ms; resistance exercise: 712.9±30.1 vs. 756.8±37.9 ms; p